Anatomical variation of the trajectory of the brachiocephalic artery encountered during parathyroid adenoma excision. A rare case report and a surgical challenge. (2019) - Zarokosta, Maria; Piperos, Theodoros; Chrysikos, Dimosthenis; Patrinos, Antonios; Kakaviatos, Dimosthenis; Kalles, Vassileios; Papapanagiotou, Ioannis; Tsiaoussis, John; Theodoropoulos, Panagiotis; Mariolis-Sapsakos, Theodoros
Highlights: BCT may present anatomical variations concerning its origin and its trajectory. Preoperative observation of these anatomical variations has vital clinical and surgical importance, since they constitute risk-factors of severe bleeding. Fundamentals to avoid iatrogenic injury are: (1) exposure of the trajectory and the origin of BCT, since it is quite evident that probable novel anatomic variations could be unexpectedly detected during the operation (2) good haemostasis and (3) preoperative utilization of diagnostic ultrasound. Abstract: Introduction: The brachiocephalic trunk (BCT), also known as the "anonymous artery" constitutes the first branch of the aortic arch that bifurcates at the level of the right sternoclavicular joint into the RCCA and the RSA. Anatomical variations of the origin and the trajectory of BCT are of vital clinical significance since they constitute major risk-factors of hemorrhage when performing tracheotomy, surgeries at the anatomic area of the neck as in the presented case. Presentation of case: A 64-year-old Caucasian female proceeded to our institution with signs and symptoms of PHPT. Imaging studies performed identified a large mass localized posterior to the right thyroid lobe. During the operation, surgeons incidentally detected anterior to the trachea aberrant trajectory of the BCT. The operation was uneventful. A meticulous review of the literature was conducted as well. Discussion: Anatomical anomalies of the origin and the trajectory of BCT are vaguely described in the literature. However, these anatomic variations constitute major risk-factors of accidental bleeding and subsequent complications when performing surgeries of the thyroid and parathyroid glands, tracheotomy and invasive radiological interventions. Conclusion: Deep knowledge of such variations of the trajectory of the BCT in addition to detailed exposure of the operative field constitute the cornerstone in order surgeons to perform a safe intervention.